Impact of postconditioning with lactate-enriched blood on in-hospital outcomes of patients with ST-segment elevation myocardial infarction. (1st October 2016) - Koyama, Takashi; Munakata, Masahito; Akima, Takashi; Kageyama, Toshimi; Shibata, Masaru; Moritani, Kazunori; Kanki, Hideaki; Ishikawa, Shiro; Mitamura, Hideo
Abstract: Background: Reperfusion injury offsets the beneficial effects of reperfusion therapy for ST-segment elevation myocardial infarction (STEMI). In our previous reports, postconditioning with lactate-enriched blood (PCLeB) induced excellent microcirculation recovery and less inflammation in STEMI patients. This study aimed to determine the in-hospital outcomes of STEMI patients treated using PCLeB. Methods: Fifty-five consecutive STEMI patients were treated using PCLeB (Age 66.6 ± 13.8 years, 76.4% men) within 12 h of symptom onset. In our modified postconditioning protocol, the duration of each brief reperfusion was prolonged from 10 s to 60 s in a stepwise manner. Lactated Ringer's solution (20–30 mL) was injected directly into the culprit coronary artery at the end of each brief reperfusion and the balloon was quickly inflated at the lesion site, whereby lactate could be trapped inside the ischemic myocardium. Each brief ischemic period lasted 60 s. After 7 cycles of balloon inflation and deflation, full reperfusion was performed. Thereafter, stenting was performed and percutaneous coronary intervention (PCI) was completed. Results: The mean corrected thrombolysis in myocardial infarction frame count was 20.1 ± 10.1 after PCI completion. The mean peak serum creatine kinase and creatine kinase-MB levels were 2751 ± 2227 IU/L and 276 ± 181 IU/L respectively. None of the study patients died during their hospital stay or required continuation of oral diuretic or inotropic therapy for heart failure on discharge. Conclusions: PCLeB led to zero in-hospital mortality and no overt heart failure on discharge in 55 consecutive STEMI patients undergoing reperfusion therapy.